2012
DOI: 10.1111/1346-8138.12024
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the pattern hair loss classifications: A comparison of the basic and specific and Norwood–Hamilton classifications

Abstract: Pattern hair loss (PHL) is the most common form of baldness in both sexes. The Norwood-Hamilton classification is the most commonly used classification worldwide, but it has many limitations. The basic and specific (BASP) classification was introduced as an improvement over the Norwood-Hamilton classification. Previous research was done to estimate the reliability of the Norwood-Hamilton classification and the result was unsatisfactory. However, the reliability of the BASP and Norwood-Hamilton classifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…So far, the problem has not been solved. Moreover, particularly in papers published by epidemiologists, reference is constantly made to the old Hamilton scale, which has been shown to be poorly reproducible …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the problem has not been solved. Moreover, particularly in papers published by epidemiologists, reference is constantly made to the old Hamilton scale, which has been shown to be poorly reproducible …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, particularly in papers published by epidemiologists, reference is constantly made to the old Hamilton scale, which has been shown to be poorly reproducible. 1,2 The difficulty in setting up reference values in human trichology depends mostly on the presence of AGA, which is well known to affect both hair density and thickness. AGA is largely widespread among adult Caucasians so much so that if one reads normality as averageness, the normal subjects should be the bald people rather than the hairy ones.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used clinical classifications to AGA include Hamilton–Norwood scale, Ludwig scale, and BASP classification. Previous studies have shown the higher concordance and repeatability of BASP classification than Hamilton–Norwood classification . On these bases, we further developed a detailed and objective quantitative grading scale.…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese study showed different ratios in various cities of china [21] . Among various classification system of hair loss, the reliability of Norwood systems vs. basic and specific patterns (BASP) have been compared which concluded that BASP was better than Norwood's classification [23] . However there are certain limitations in BASP classification too, i.e., certain types of fronto-parietal and vertex regions (F2, F3) are confused with type v. and type V of BASP is confused with Type V in Norwood system.…”
Section: Discussionmentioning
confidence: 99%